2017
DOI: 10.1111/hiv.12502
|View full text |Cite
|
Sign up to set email alerts
|

Liver‐related mortality and hospitalizations attributable to chronic hepatitis C virus coinfection in persons living with HIV

Abstract: Chronic HCV infection increases the risk of liver-related mortality and liver-related hospitalizations in PLWH, despite good control of HIV infection. Sixty per cent of liver-related mortality in chronically HCV-coinfected PLWH could be attributable to chronic HCV infection. The effect of mass HCV eradication with new therapies should be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…However, fifty percent of patients with grade 3–4 AEs suffered from chronic hepatitis C and a significant higher proportion of patients with positive HCV-RNA experienced liver AE. We confirmed a low incidence of liver events in patients initiating EVG/COBI/FTC/TDF a described in RCTs [14] and the higher rates of abnormal AST and ALT and liver decompensation in antiretroviral treated patients with HIV-HCV coinfection as described in literature [14, 15]. Data are lacking about specific hepatic toxicity of EVG/COBI in patient with chronic HCV viral hepatitis.…”
Section: Discussionsupporting
confidence: 86%
“…However, fifty percent of patients with grade 3–4 AEs suffered from chronic hepatitis C and a significant higher proportion of patients with positive HCV-RNA experienced liver AE. We confirmed a low incidence of liver events in patients initiating EVG/COBI/FTC/TDF a described in RCTs [14] and the higher rates of abnormal AST and ALT and liver decompensation in antiretroviral treated patients with HIV-HCV coinfection as described in literature [14, 15]. Data are lacking about specific hepatic toxicity of EVG/COBI in patient with chronic HCV viral hepatitis.…”
Section: Discussionsupporting
confidence: 86%
“…A total of 1984 PLHIV initiating ART and were tested for HBV and HCV at baseline (Table 1). The median age of patients was 39 years (IQR [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49], and the median CD4+ T-cell count was 152 cells/mm 3…”
Section: Demographic Characteristics and Hepatitis Infection At Basmentioning
confidence: 99%
“…37 Our finding concurs with the previous studies that mortality rate in HCV/HIV co-infected patients was significantly higher than HIV/HBV co-infected patients. 38,39 Second, a common side-effect of NNRTI drugs is liver toxicity which is associated with the hepatotoxicity rate especially in patients with prior liver disease. 40,41 A previous study showed that NVP leads to the serious liver damage and druginduced liver fibrosis especially in patients with hepatitis C. [42][43][44] Third, the characteristics of the susceptible population who are likely to be co-infected HCV also contribute to increasing mortality risk and hepatotoxicity risk.…”
Section: Association Between Hepatotoxicity and Hepatitis Co-infectmentioning
confidence: 99%
“…[9][10][11][12] Advanced liver disease accounted for 13% of all deaths among PLWH prior to treatment with direct-acting antivirals (DAAs), and in the US chronic HCV infection has been shown to be the leading cause of liver disease and related mortality in coinfected individuals. [13][14][15][16][17] In the past, persons with HIV/HCV coinfection achieved lower rates of sustained virologic response (SVR) after use of interferon and ribavirin HCV treatment compared with those with HCV mono-infection. [5] In addition to poor efficacy, older HCV treatment regimens were associated with many adverse effects such as depression, anemia, flu-like symptoms, and were often contraindicated due to additional comorbidities within the PLWH.…”
Section: Introductionmentioning
confidence: 99%